Unveiling behavioral and molecular neuroadaptations related to the antidepressant action of cannabidiol in the unpredictable chronic mild stress model - García-Gutiérrez, María Salud; Navarro, Daniela; Austrich-Olivares, Amaya; Manzanares, Jorge (Frontiers in Pharmacology, 2023)
Introduction: This study aims to further characterize cannabidiol’s pharmacological and molecular profile as an antidepressant. Methods: Effects of cannabidiol (CBD), alone or combined with sertraline (STR), were evaluated in male CD1 mice (n=48) exposed to an unpredictable chronic mild stress (UCMS) procedure. Once the model was established (4 weeks), mice received CBD (20 mg·kg-1, i.p.), STR (10 mg·kg-1, p.o.) or its combination for 28 days. The efficacy of CBD was evaluated using the light-dark box (LDB), elevated plus maze (EPM), tail suspension (TS), sucrose consumption (SC) and novel object recognition (NOR) tests. Gene expression changes in the serotonin transporter, 5-HT1A and 5-HT2A receptors, BDNF, VGlut1 and PPARdelta, were evaluated in the dorsal raphe, hippocampus (Hipp) and amygdala by real-time PCR. Besides, BDNF, NeuN and caspase-3 immunoreactivity were assessed in the Hipp. Results: CBD exerted anxiolytic and antidepressant-like effects at 4 and 7 days of treatment in the LDB and TS tests, respectively. In contrast, STR required 14 days of treatment to show efficacy. CBD improved cognitive impairment and anhedonia more significantly than STR. CBD plus STR showed a similar effect than CBD in the LBD, TST and EPM. However, a worse outcome was observed in the NOR and SI tests. CBD modulates all molecular disturbances induced by UCMS, whereas STR and the combination could not restore 5-HT1A, BDNF and PPARdelta in the Hipp. Discussion: These results pointed out CBD as a potential new antidepressant with faster action and efficiency than STR. Particular attention should be given to the combination of CBD with current SSRI since it appears to produce a negative impact on treatment.